2022
DOI: 10.1080/19490976.2022.2132903
|View full text |Cite
|
Sign up to set email alerts
|

Formation of secondary allo-bile acids by novel enzymes from gut Firmicutes

Abstract: The gut microbiome of vertebrates is capable of numerous biotransformations of bile acids, which are responsible for intestinal lipid digestion and function as key nutrient-signaling molecules. The human liver produces bile acids from cholesterol predominantly in the A/B- cis orientation in which the sterol rings are “kinked”, as well as small quantities of A/B- trans oriented “flat” stereoisomers known as “primary allo-bile acids”. While the complex multi-step bil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 65 publications
4
20
0
Order By: Relevance
“…The current CA 7-DH-ion pathway would suggest that this gene is not involved in that process in strain VPI 12708 [24], which is consistent with the low level of expression observed here (Figure 7B). Conversely, its high level of upregulation in strain ATCC 35704 matches previously published data [21,33] and suggests that baiJ may play a role in the 7-DH-ion of CA or other BAs in that strain as it does with CDCA [21,43]. Finally, E. muris SJ24, the murine isolate, barely registered any bai gene expression response to CA or any other BA tested.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The current CA 7-DH-ion pathway would suggest that this gene is not involved in that process in strain VPI 12708 [24], which is consistent with the low level of expression observed here (Figure 7B). Conversely, its high level of upregulation in strain ATCC 35704 matches previously published data [21,33] and suggests that baiJ may play a role in the 7-DH-ion of CA or other BAs in that strain as it does with CDCA [21,43]. Finally, E. muris SJ24, the murine isolate, barely registered any bai gene expression response to CA or any other BA tested.…”
Section: Discussionsupporting
confidence: 83%
“…From genome analysis, E. muris SJ24 has fragments of baiJKL as pseudogenes. The exact role of these genes has yet to be de ned although there is novel evidence of the role of BaiJ [43].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed the involvement of two types of bacterial steroid dehydrogenases, namely 5α-reductase (3-oxo-5α-steroid 4-dehydrogenase, 5AR) and 5β-reductase (3-oxo-5β-steroid 4-dehydrogenase, 5BR), in the production of homologous (5α and 5β) BAs. 62 The levels of isolithocholic acid (isoLCA), 3-oxolithocholic acid (3-oxoLCA), allolithocholic acid (alloLCA), 3-oxoallolithocholic acid (3-oxoalloLCA), and isoalloLCA were also found to be significantly higher in the centenarian group (average age, 107 years old) due to the unique gut microbiota in centenarians. 25 Analysis of centenarians’ gut microbiota revealed the presence of many strains with strong 3α-HSDH, 3β-HSDH, 5AR, and/or 5BR activity.…”
Section: Mechanisms Of Bile Acid Biotransformation By Gut Microbiotamentioning
confidence: 99%
“…A baiJKL operon is found in some organisms, where baiK encodes a bile acid CoA transferase and BaiJ is a flavoprotein that was shown to be involved in the formation of allo-bile acids. 15 , 16 Indeed, a homologue of BaiJ (named BaiP by authors) found in other organisms, was likewise shown to be a bile acid 5α-reductase leading to allo-bile acid production. 16 BaiN is a flavoprotein that may play a role in the reductive part of the 7α-dehydroxylation pathway and the baiN gene is consistently found next to baiO which encodes a NAD(FAD)-utilizing dehydrogenase for which a role in bile acid metabolism has yet to be shown.…”
Section: Introductionmentioning
confidence: 94%